Numerical study of boundary layer due to stationary flat plate - Mohamad Khairull Izzuan, Mohd Idris (2007)
This thesis presents the numerical study on boundary layer equation due to stationary flat plate. Matlab is the mathematical programming that used to solve the boundary layer equation applied of keller box method. The objective of this project is to solve the boundary layer equation on the stationary flat plate utilizing the Matlab programming software. Matlab source codes are generated base on boundary layer equation. Then it was compiled and analyzes using Matlab. The result for Matlab is compared to the Blasius solution. It is largest deviation is about 0.070% and lowest is 0.005%. The present result compared with the Blasius solution and it can be seen that the both result are good agreement.